2020
DOI: 10.1002/14651858.cd009209.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Workplace pedometer interventions for increasing physical activity

Abstract: BackgroundThe World Health Organization and the World Economic Forum have recommended further research to strengthen current knowledge of workplace health programmes, particularly on effectiveness and using simple instruments. A pedometer is one such simple instrument that can be incorporated in workplace interventions. ObjectivesTo assess the effectiveness of pedometer interventions in the workplace for increasing physical activity and improving subsequent health outcomes. Search methods Electronic searches o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 161 publications
0
31
0
2
Order By: Relevance
“…However, it is notable that the increase of 906 steps per day falls short of the Step Count Challenge integrated goal setting target of increasing steps by 5000 steps on five days per week from week 1 by the end of the intervention. Further, these step changes are less than the daily step count change from baseline to end of intervention reported in review level evidence (+1900) [19], by the Global Corporate Challenge (+2149) [20], Stepathlon (+3519) [22], and a previous small-scale (n = 20) Step Count Challenge evaluation (+1487) [23]. These differences in the other studies may at least partially be explained by the inclusion of a true baseline measurement point in these other studies, which is not elevated by the commencement of the intervention.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…However, it is notable that the increase of 906 steps per day falls short of the Step Count Challenge integrated goal setting target of increasing steps by 5000 steps on five days per week from week 1 by the end of the intervention. Further, these step changes are less than the daily step count change from baseline to end of intervention reported in review level evidence (+1900) [19], by the Global Corporate Challenge (+2149) [20], Stepathlon (+3519) [22], and a previous small-scale (n = 20) Step Count Challenge evaluation (+1487) [23]. These differences in the other studies may at least partially be explained by the inclusion of a true baseline measurement point in these other studies, which is not elevated by the commencement of the intervention.…”
Section: Discussionmentioning
confidence: 83%
“…Future research could consider how best to attract more men and low active participants to the intervention. Previous research suggests that longer term behavior change is minimal with workplace pedometer interventions [19], so further Step Count Challenge research that collects data beyond the eight weeks of the challenge would be useful to understand the potential longer term behavior change benefits of participation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…“We included [search strategies] used in other systematic reviews for research design [ 111 ], setting [ 112 , 113 ], physical activity and healthy eating [ 114 116 ], obesity [ 111 ], tobacco use prevention [ 117 ], and alcohol misuse [ 118 ]. We also used a search [strategy] for intervention (implementation strategies) that had been employed in previous Cochrane Reviews [ 119 , 120 ], and which was originally developed based on common terms in implementation and dissemination research.” [ 121 ]…”
Section: Part 3: Explanation and Elaborationmentioning
confidence: 99%
“…This one study on walking showed that a workplace walking intervention could positively influence work productivity in employees with low initial steps counts [21]. In a more recent review of workplace pedometer intervention by Freak-poli et al 2020, 14 studies were included with none measuring work-related outcomes [22]. When looking specifically at stress as an outcome of interest to workplaces, a review by Chu et al 2014.…”
Section: Introductionmentioning
confidence: 99%